Konsumsi dan Kebutuhan Air Selada Pada Teknik Hidroponik Sistem Terapung - Riani Muharomah; Budi Indra Setiawan; Muhammad Yanuar J. Purwanto (Jurnal Irigasi, 2017)
Floating hydroponic system (THST) is a hydroponic technique that its planting medium is placed on a floating styrofoam in a large pool that contains the nutrient solution. The common obstacles faced by this hydroponic technique is the absence of additional water during the growing season, so the water level in the pool is shrinking as the water is consumed by the plants. This study was to determine the rate of water consumption that fluctuated during the planting period and the water requirements which is necessary to maintain the water level. We found the averaged of lettuce water consumption was 0.74 mm/day. The accumulated water consumption for 54 days in two periods of growing season was 40 mm. The rate of lettuce water consumption at the beginning of the planting season was the smaller amounted to 0.75 mm/day and the greatest appeared at the end of the growing season equal to 2.09 mm/day. Finally, the water requirements to maintain the water level initially is 0.76 liters/day/m2 and then increase until reaches 2.09 liters/day/m2 at the end of the growing season or it is equivalent to 7.59 m3 per 90 m2 planting area.